Peter Burke um historiador da cultura e da sociedade: as muitas faces de um intelectual polímata - Soares Junior, José Roberto (2016)
This study is focused on the life and academic work of the British historian Peter Burke, a subject historical holder of an extensive and multiple work. To understand it, we set out to look for the fundamental categories that give meaning to his work as a historian. So through the nodes that support his work, it becomes possible to understand that each specific analyzed here is part of that classify as the universality of the author's work. The method used here was to let the author speak, that is, we always start historian Peter Burke to get to our actual analysis. His career was and is always marked by the presence in academic environments, from a young age was interested in history and the arts. He studied at Oxford, taught at Sussex and later moved to Cambridge, where he is professor emeritus already retired. It was one of the first historians concerned effectively to promote interdisciplinarity between history and its sister sciences, such as sociology, anthropology, geography and others. It is an expert historian in European history; Italian Renaissance; cultural history; history of languages; history of knowledge, always concentrate these studies between "culture" and "society" specifically the fifteenth century to the eighteenth. In its original historiographical school, English, developed and could enjoy from the presence of historians like Christopher Hill, Eric Hobsbawm, E. P. Thompson and his tutor Keith Thomas. Outside his school sought innovations in Annales, was greatly influenced by Fernand Braudel, was concerned with the history of "high culture", always thought of as not devoid of circularity which Bakhtin preached. Today is the greatest exponent of the English cultural story, a polymath authentic. In Brazil, taught at USP as a visiting professor from 1994-95, is married to Brazilian Professor Maria Lucia Garcia Pallares-Burke 27 years ago, sharing with her interest in the work of the sociologist Gilberto Freyre. Currently has more than thirty books published in Portuguese, almost all in Brazil